Utilization of Village Funds Based on Planning in Development in Improving Village Autonomy and Welfare of Village Communities in Malang Regency - Maryunani Maryunani; Tri Cahyono; Badrul Jamal (AIBPM Publisher, 2024)
This study aims to analyze how the impact of using Village Funds for village independence and community welfare in Sumberpasir and Pucangsongo Villages, Pakis District, Malang Regency based on community perceptions using the Sustainable Livelihood Approach (SLA) approach. The selection of the two villages was based on consideration of the uniqueness of different characters, where Sumberpasir is tourism-based because it is on the route of Bromo Tengger Semeru National Park (TNBTS) while Pucangsongo is agriculture-based. The results of the analysis show that in Sumberpasir Village, the impact of village utilization is more prominent on social capital, namely in the form of collaboration with other communities and human capital in the form of training for technology. In Pucangsongo Village, the use of village funds for the independence and welfare of rural communities is influenced by financial capital, in the form of business capital assistance for farmer groups. In addition, natural capital factors are also prominent as the use of village funds also to support the agricultural sector. This research contributes to an empirical study that provides an understanding that the utilization of village funds can be heterogeneous based on the characteristics of each village.